Gambaran magnesium serum pada pekerja bangunan - Mudeng, Gloria N.L.; Paruntu, Michaela E.; Assa, Youla A. (Universitas Sam Ratulangi, 2016)
Abstract: Magnesium is one of the makroelemen body needs in large quantities and the fourth most electrolyte in the body. Vigorous activity could lead to change magnesium levels. The aim of this study was to determine the serum magnesium levels in construction workers. The study was conducted in a descriptive cross sectional arrangement with thirty respondents who were eligible to the inclusion criteria. Samples were taken using a total sampling methods. The results showed 29 respondents (96,67%) with a normal serum magnesium levels of 1,6-2,6 mg/dL and 1 repondent (3,33%) with low serum magnesium levels. Conclusion: Most of the serum magnesium levels in construction workers are in normal limits.Keywords: serum magnesium levels, construction workers, vigorous activity.Â Abstrak : Magnesium merupakan salah satu makroelemen yang dibutuhkan tubuh dalam jumlah besar dan merupakan elektrolit keempat terbanyak dalam tubuh. Aktivitas fisik berat dapat merubah kadar magnesium dalam tubuh. Tujuan penelitian ini adalah untuk mengetahui gambaran kadar magnesium serum pada pekerja bangunan. Penelitian bersifat deskriptif dengan pendekatan potong lintang dengan sampel berjumlah 30 orang sesuai dengan kriteria inklusi. Metode pemilihan sampel menggunakan cara total sampling. Hasil penelitian dengan nilai rujukan normal 1,6-2,6 mg/dL didapat 29 orang (96,67%) dengan kadar normal dan 1 orang (3,33%) dengan kadar magnesium serum rendah. Simpulan: Sebagian besar kadar magnesium serum pada pekerja bangunan ada dalam batas normal. Kata kunci: kadar magnesium serum, pekerja bangunan, aktivitas fisik berat.